Fetal and postnatal zinc restriction: Sex differences in metabolic alterations in adult rats - Mendes Garrido Abregú, Facundo (2019)
Objective: Intrauterine and postnatal micronutrient malnutrition may program metabolic diseases in adulthood. We examined whether moderate zinc restriction in male and female rats throughout fetal life, lactation, or postweaning growth induces alterations in liver, adipose tissue, and intermediate metabolism. Methods: Female Wistar rats were fed low-zinc or control zinc diets from pregnancy to offspring weaning. After weaning, male and female offspring were fed either a low-zinc or a control zinc diet. At 74 d of life, oral glucose tolerance tests were performed and serum metabolic profiles were evaluated. Systolic blood pressure and oxidative stress and morphology of liver and retroperitoneal adipose tissue were evaluated in 81 d old offspring. Results: Zinc restriction during prenatal and postnatal life induced an increase in systolic blood pressure, hyperglycemia, hypertriglyceridemia, higher serum glucose levels at 180 min after glucose overload, and greater insulin resistance indexes in male rats. Hepatic histologic studies revealed no morphologic alterations, but an increase in lipid peroxidation and catalase activity were identified in zinc-deficient male rats. Adipose tissue from zinc-deficient male rats had adipocyte hypertrophy, an increase in lipid peroxidation, and a reduction in catalase and glutathione peroxidase activity. Adequate dietary zinc content during postweaning growth reversed basal hyperglycemia, hypertriglyceridemia, insulin resistance indexes, hepatic oxidative stress, and adipocyte hypertrophy. Female rats were less sensitive to the metabolic effects of zinc restriction. Conclusions: This study strengthens the importance of a balanced intake of zinc during growth to ensure adequate lipid and carbohydrate metabolism in adult life.